Asymmetric clipped optical OFDM adaptive indexing modulation scheme under turbulent channels - WANG Huiqin; PEI Yanhao; WANG Zhen; TANG Qihan; RU Hui; ZHANG Hongyan (Tongxin xuebao)
Given the issue that existing optical orthogonal frequency division multiplexing (OFDM) with index modulation (OOFDM-IM) struggle to adapt to channel variations, which results in limitations on transmission rate. A threshold optimization model aimed at maximizing transmission rate was constructed. By dynamically identifying the optimal M-QAM modulation switching threshold, an optical OFDM adaptive indexing modulation scheme was proposed. After a detailed introduction to the mapping principle of the signal, the optimal threshold and theoretical bit error rate under different turbulence intensities were derived. The simulation results show that compared with traditional OOFDM-IM schemes, the proposed scheme significantly enhances transmission rate while satisfying the target bit error rate.